Stress Resources and Responses of Student-Athlete Counseling Services Clients, Non-Student-Athlete Clients and Non-Athlete Clients - Etzel, Edward F.; Lantz, Christopher D. (My University, 1999)
It is widely believed that because of the unique demands of their lifestyles, college student-athletes often experience greater levels of life-stress than do non-athlete students. For the purpose of this study stress was considered a complex process characterized by the presence of various stress sources, perceptions of threat or danger to self, and cognitive, affective and/or behavioral, and physical reactions to these phenomena (Spielberger, 1989). Accordingly, stress response may be manifested cognitively (e.g., worry), behaviorally (e.g., avoidance behaviors), emotionally (e.g., depression), or somatically (e.g., muscle aches). Limited research on this topic has provided inconsistent support for this notion. Quick Stress Questionnaire (QSQ) responses of student-athlete counseling service clients, non-athlete student counseling service clients, and a non-client sample were compared to examine differences in the frequency and severity of life-stress and life-stress responses. Quick Stress Questionnaire (QSQ) (Otani, 1985) of student clients were obtained from the counseling service closed files at a medium sized, land grant institution. The QSQ is a problem checklist completed by clients, as a routine part of all intake assessments and becomes a part a each student's permanent, confidential file. Clients did not provide consent to access their QSQs. The QSQs of 91 athlete clients (i.e., those student-athletes who had sought counseling) were examined, although a random sample of 207 QSQs was obtained from the non-athlete client population over a three-year period. These two sets of QSQ data were compared with non-athlete, non-client QSQ student norms (N=218) developed from the general student population over the same period of time. All groups reported moderate to moderately high stress levels, but student-athletes reported fewer sources of distress and fewer serve stress-related symptoms than non-athlete clients or non-clients. Interestingly, student athlete clients reported lower financial related distress than non athlete clients and non clients. Findings were discussed in the context of the student-athlete lifestyle and recommendations for further study were provided.
Keywords: stress; academic support